(untitled) (Journal of Advanced Research in Civil Engineering and Architecture, 2019)
Construction management is a very important process in order to achieve the objectives of every project in terms of time, cost, quality, and insured safety. But most recent studies most researchers have been focusing on the management of risks rather than identifying the critical risks involved in construction projects. This paper aims to identify the major risks associated with construction projects that expected to affect project performance during the project life cycle in Ethiopia. Various risk factors in construction projects were identified from the literature. Questionnaire survey and interview method was used to collect data from the respondents. The relative importance index (RII) was used for data analysis to identify the major variables. Based on the analysis of the likelihood of occurrence of the risks, this paper identified the critical risks in construction projects in Ethiopia. The research found that the critical risks were mainly unforeseen site conditions, improper design, incomplete contract documents, inflation, lack of timely decision making, scope change, political instability, payment delay, lack approvals, corruption, and poor contract administration. Finally conclusions made from the finding and recommendations forwarded to minimize risks in construction projects.